The Influence of Experiential Marketing on Visitors’ Satisfaction and Intention to Revisit at Batur Camp Bali - Yogiswari, Ni Made Mas; Suryawardani, I Gusti Ayu Oka; Wiranatha, Agung Suryawan (Institut Pariwisata dan Bisnis Internasional, 2021)
Experiential marketing which consists of sense, feel, think, act, and relate is a marketing approach that can generate sensations and experiences, can be used to create tourist satisfaction and become the basis of revisit intention. The purpose of this study is to analyze the influence of experiential marketing to satisfaction and revisit intention. The data in this study were obtained through distributing questionnaires by online to 100 respondents who had experienced on undertook camping at the Batur Camping Ground. Data were analyzed using the SmartPLS based on Structural Equation Modeling (SEM) method. The results showed that sense, feel, act, and relate significantly influence satisfaction. Feel, think, and relate significantly influence revisit intention. Tourist satisfaction significantly influence tourists' intention to revisit. This study suggests that Batur Camping Ground management must improve services in order to keep maintaining tourist satisfaction and increase tourists' decision in undertaking camping.